Dexamethasone may affect the occurrence of parenteral nutrition-associated cholestasis in preterm neonates - Saizhi Jiang; Qingqing Hu; Jing Zhang (Frontiers Media S.A., 2022)
IntroductionGlucocorticoids are currently used for the co-therapeutic management of autoimmune hepatitis and some cholestatic diseases. Thus far, we do not know the efficacy of glucocorticoids in the treatment of parenteral nutrition-associated cholestasis. We aimed to analyze whether the administration of late postnatal dexamethasone for treating bronchopulmonary dysplasia influence the occurrence of parenteral nutrition-associated cholestasis in preterm neonates.MethodsA retrospective study was conducted for 78 preterm neonates without major anomalies (gestational age was <30 weeks, and birthweight was ≤1000 g) hospitalized in a neonatal unit. Total and direct serum bilirubin levels were measured about every two weeks for all neonates. Data including the administration of dexamethasone, intravenous nutrition, and enteral feeding were collected by at least three audits.ResultsA total of 15 preterm neonates were diagnosed with parenteral nutrition-associated cholestasis, and after stopping parenteral nutrition, the direct bilirubin value decreased to the normal level for no longer than 150 days. The prolonged duration of parenteral nutrition was a risk factor, and late postnatal dexamethasone treatment was a protective factor in reducing the incidence of parenteral nutrition-associated cholestasis.ConclusionDexamethasone treatment may reduce the occurrence of parenteral nutrition-associated cholestasis in preterm neonates.